Sucesso de projetos de transformação digital: uma análise comparativa das metodologias de gerenciamento de projetos e proposição de modelo - Novaes, Graziela Fontes (2025)
Digital transformation is materialized through projects aimed at introducing innovation into companies' business processes. These projects are embedded in a dynamic environment characterized by high complexity and uncertainty. Given that the management method serves as a means of addressing environmental influences, the choice of an appropriate methodology can mitigate the volatile negative effects of the digital transformation environment and enhance project success. This research seeks to answer the following question: How should a model for managing digital transformation projects be structured to contribute to their success? Thus, this thesis aims to propose a model for managing digital transformation projects that enhances the likelihood of their success. To achieve this objective, two studies were conducted. The first study, carried out through a systematic literature review, aimed to analyze existing research on project management methodologies in the context of digital transformation. As a result, it identified benefits and challenges associated with the use of traditional, agile, and hybrid methodologies for managing digital transformation projects. The second study, based on a survey with a sample of 299 respondents, sought to determine whether traditional, agile, or hybrid methodologies influence the success of digital transformation projects. The results indicated that the traditional methodology positively influences the success of digital transformation projects, whereas the agile and hybrid methodologies did not demonstrate a statistically significant impact. Beyond its theoretical contribution, this thesis resulted in the development of a technical technological product, which consists of a model for managing digital transformation projects. This model, classified as a non-patentable process, provides structured guidelines to assist managers in selecting the most appropriate approach and mitigating specific challenges in digital transformation projects. Accordingly, this thesis provides insights for both academics and professionals in project management, particularly in the context of digital transformation, offering practical recommendations based on evidence collected throughout the conducted studies. From a theoretical perspective, the research expands the literature on project management in digital transformation, presenting a comparative analysis of traditional, agile, and hybrid methodologies. For professional practice, it offers an applicable model that supports the maximization of project success.